Effectiveness of Cooperative Scramble Learning Model on Imroving Learning outcomes - Denis, Sourbron; Lena, Roy; Erkka, Käräjämäki (World Psychology, 2023)
There are many effective learning models used in education, one of which is the cooperative scramble learning method. Cooperative scramble is a learning model where students learn in groups that help them solve learning problems given by the teacher. With that, this study aims to determine the benefits of the cooperative scramble learning model to increase learning effectiveness. Students are often bored because educators only use only the lecture method without any creativity to develop more effective and innovative learning models. The type of method used in this research is quantitative by conducting surveys and in-depth interviews. The results of this study explain that the cooperative scramble method is very effective for students. The conclusion of this research is that educators can utilize the cooperative scramble method to improve learning outcomes based on evidence of a student's learning achievement and interest in learning. The limitation of this study is that researchers only conduct research with the cooperative scramble learning model, researchers hope that further research uses other learning models so that student learning outcomes are maximized.